(untitled) (PerCursos, 2025)
The "Nós Propomos! Citizenship and Innovation in Geographical Education" Project (PNP!) was conceived in the academic years of 2011 and 2012 at the Institute of Geography and Spatial Planning (IGOT) of the University of Lisbon (UL), with the aim of improving geographical education. It seeks to promote the articulation and commitment of schools—and the Geography discipline in particular—with the resolution of local socio-environmental issues. To this end, the PNP! introduces discussions in schools that foster citizenship and the construction and appreciation of territorial citizenship. The project is characterized by simple concepts, methods, and methodologies, such as case studies, problem-based learning, and socio-environmental themes. Therefore, understanding the guidelines of the PNP! is crucial for its integration and development in Geography classes in Basic Education. This research aims to characterize three core principles of the "Nós Propomos!" Project: the case study, problem-based learning, and socio-environmental themes. Additionally, it seeks to highlight the relevance and proposals for constructing geographical knowledge based on the project’s principles. The objectives of this research are supported by a bibliographical review and the systematization of the theoretical framework. This research shows that the project develops positive pathways for geographical education by proposing innovative and diverse methods aimed at fostering the students’ territorial citizenship.